Expression analysis of a panel of cancer-testis antigens in bladder cancer. (26th October 2018) - Yazarlou, Fatemeh; Kholghi-Oskooei, Vahid; Afsharpad, Mandana; Nekoohesh, Leila; Moharrami, Tamouchin; Rad, Hanie M; Ghafouri-Fard, Soudeh; Modarressi, Mohammad H
Aim: Cancer-testis antigens (CTAs) have specific expression in gametogenic tissues and aberrant expression in cancers.Materials & methods: We assessed expression of five testis-specific genes namely KIF2B, CST8, TMEM225, RBM46, OAZ3 in bladder cancer tissues, adjacent non-neoplastic tissues and urinary cell pellets (UCPs) of bladder cancer patients compared with nonmalignant conditions.Results: Expressions of all CTAs were higher in UCPs of bladder cancer patients compared with nonmalignant conditions. RBM46 expression in UCPs was higher in patients with recurrent tumors compared with primary tumors and in patients without hematuria compared with those having hematuria. TMEM225 expression in tumoral tissues was higher in high-grade tumors compared with low-grade tumors.Conclusion: Expression analysis of CTAs in UCP might provide diagnostic information about bladder cancer.